Measuring the Level of Prevalence of Undernourishment (PoU) - Iwang, Baso; Sa’at, Nor Hayati Binti; Anwar, Andi Faisal; Rusydi, Bahrul Ulum (Faculty of Economics and Business Universitas Jenderal Soedirman, 2024)
Prevalence of Undernourishment (PoU) is an indicator that measures the achievement of Sustainable Development Goal’s 2nd goal. Empirical evidence shows that in 2018-2022) Indonesia’s PoU continued to increase. Therefore, this study aims to determine factors that influence the level of PoU in Indonesia through food expectations, producer price index, food security budget, community purchasing power, and social assistance in the food sector. The novelty of this study is trying to trace the relationship between those variables towards Indonesia's PoU. To achieve this goal, multiple regression analysis was used with secondary data. The results show that the producer price index, food security budget, and community purchasing power had a significant effect on Indonesia's PoU level. Meanwhile, food expectations and social assistance did not have a significant effect on Indonesia's PoU level. This study implies that the government needs to evaluate various food security programs to maximize the reduction of Indonesia's PoU.